ULAMAS CONTRIBUTIONS IN FACING THE COVID-19 PANDEMIC - Rizka Harfiani (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of the study was to analyze the contribution of scholars who are members of Islamic organizations in Indonesia in determining policies and efforts to deal with the Covid-19 pandemic that hit the world, including in Indonesia. This qualitative research uses library research methods, with data collection techniques based on research results in journals, magazines and articles on social media. The data analysis technique used is descriptive analysis. While the technique of checking the validity of the data uses a credibility test, namely increasing persistence by using reference materials. The results of the research related to the contribution and role of Indonesian ulama in dealing with the Covid-19 pandemic were carried out on scholars who were involved in six major organizations in Indonesia, namely Muhammadiyah, Majelis Ulama Indonesia (MUI), Al-Irsyad Al-Islamiyah, Dewan Masjid Indonesia (DMI), Ikatan Cendikiawan Muslim Indonesia (ICMI), and Nahdlatul Wathan. The six organizations are expected to be able to represent the many Islamic organizations in Indonesia, all of which play an active role together against Covid-19, in providing solutions for handling the impact of Covid-19 in various aspects of people's lives.Keywords: contribution, pandemic, ulama.